A Corpus-Based Study of Grammatical Collocation on Asian EFL Learners - Paris, Nirma; Samad, Pratiwi; Namchan, Monsinee (Institut Agama Islam Negeri Parepare, 2023)
This article presents a corpus-based study that investigated grammatical collocations. The study aimed to examine and analyze grammatical collocations employed by Asian EFL learners at Khon Kaen University in Thailand. An Asian learner corpus was built with 38,338 tokens from 20 academic writing papers of Asian EFL learners. The written learner corpus consists of Thai, The Chinese, Indonesian, and The Philippines of academic papers. CLAWS tagger, AntConc (Windows 3.4.4), and manual analysis were used to analyze the data. The results of the study found that grammatical collocations employed by Asian EFL learners at Khon Kaen University were 1,941 tokens of noun + preposition, 467 tokens of verb + preposition, 147 tokens of adjective + preposition, and none of preposition + noun was used in the papers. The study also revealed that the learners used similar prepositions in the top 10 frequency, but the arrangement order was different. In addition, there were a few of the same collocated words that used by the learners from each country.